Aplicabilidade clínica da técnica CRISPR-Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats) no tratamento da anemia falciforme: uma revisão integrativa - Mataveia, Elly Raquelina Flor (Universidade Federal de São Carlos, 2020)
Introduction and objective: Sickle cell disease is the most common hemoglobinopathy in humans and has a high morbidity and mortality rates. It is caused by a point mutation, an A-T substitution (GAG→GTG) in the first exon of the β-globin gene, which determines the replacement of glutamate for valine at position 6 of the protein chain, giving rise to a structural variant of hemoglobin (HbS), causing, under hypoxia conditions, erythrocytes to acquire a sickle shape compromising the efficient oxygen transport. The treatments widely available at the moment only ease the complications of the disease. In this context, the CRISPR-Cas9 technology, which allows gene editing directly into DNA, appears as a solution that allows the mutation to be corrected and/or improve fetal hemoglobin expression. This systematic integrative review aimed to answer the following question: what is the clinical applicability of the CRISPR-Cas9 technology in the treatment of sickle cell disease? Methodology: Theoretical or empirical studies, primary or secondary, developed with qualitative, quantitative or mixed methodology, published until November 15th 2020, in English, which portrays the theme related to this review were selected. The research was carried out in three databases based on descriptors chosen by the “Medical Subject Headings”. Results: Initially, 79 primary studies were identified. With the exclusion of repeated articles in different databases, 75 studies remained, which were evaluated based on their titles and abstracts, and 28 articles were then selected. These 28 articles were read in full and 10 articles were excluded. Thus, 18 articles were selected at the end of this review. No clinical studies have been identified. It is observed that 12 articles are narrative reviews of in vitro or preclinical studies that discuss the clinical applicability; 4 studies are qualitative or descriptive studies about the theme; and 2 studies are opinion articles. The selected studies showed that in vivo (in animal models) and in vitro, the CRISPR-Cas9 technology is able to correct the mutation that causes sickle cell disease and/or increase the levels of fetal hemoglobin expression. However, in vivo, the challenges are to avoid toxicity, off-target effects and ensure the efficiency of the transplant. Patients, family members, researchers and health professionals are predisposed to participate in clinical trials involving CRISPR-Cas9, but do not have enough knowledge about the subject. Conclusions: The CRISPR-Cas9 technology has great potential for clinical use in the treatment of sickle cell disease. It is necessary to educate the population about the fundamentals of gene editing, thus facilitating its acceptance and availability in regard to clinical trials. An additional concern is the ethical regularization of the use of this technology in human beings.
Clinical applicability of the CRISPR-Cas9 technology (Clustered Regularly Interspaced Short Palindromic Repeats) in the treatment of sickle cell anemia: an integrative review
Keywords: CRISPR; Proteína 9 Associada à CRISPR; Anemia falciforme; Revisão integrativa; CRISPR-Associated Protein 9; Sickle cell disease; Integrative review; CIENCIAS BIOLOGICAS::GENETICA::GENETICA HUMANA E MEDICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS